The Role of Intersentential Connectives in Complex Narrative Discourse: Katherine Mansfield's "The Garden Party" - Pilar Alonso Rodríguez (Miscelánea: A Journal of English and American Studies)
This paper explores the role of intersentential connectives in complex narrative discourse so as to investigate the applicability of recent findings in the literature to more complex data than that usually found in theoretical studies of the phenomenon. For this purpose the function of connectives in Katherine Mansfield’s short story “The Garden Party” will be analysed, concentrating mainly on the intersentential connectives AND and BUT which are unusually salient and recurrent throughout the text. The analysis shows that both connectives provide a means of attaining local and global cohesion, and, most important, they efficiently serve as explicit signals for the development and construction of all participants’ mental representations of the story.